2019
DOI: 10.1080/02699052.2019.1565895
|View full text |Cite
|
Sign up to set email alerts
|

NFL blood levels are moderated by subconcussive impacts in a cohort of college football players

Abstract: Repetitive subconcussive head impacts in contact/collision sports such as American football may contribute to long-term brain changes. However, the lack of data to measure the effects of repeated subconcussive blows limits our understanding of their potential contributions to neuropathological alterations including neuronal damage. Here we examined the impact of subconcussive head impacts as measured by an accelerometer embedded mouth guard on changes in blood levels of the neuronal protein neurofilament light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 24 publications
1
42
1
Order By: Relevance
“…Similar to tau protein, NfL functions as a scaffolding structural protein in axonal and dendritic branching and growth, and NfL undergoes post-translational modification by a series of phosphorylation events, which can make it vulnerable to mechanical stretch and shear stress (62). Growing evidence supports that NfL levels in blood have shown to reflect the progression of neurodegenerative condition (e.g., Alzheimer's disease, multiple sclerosis) ( [63][64][65], differentiate severities of TBI (66), predict clinical outcome (e.g., functional recovery, return-to-play) after severe TBI and concussion (67,68), and correlate with subconcussive head impact exposure (24,26,32,33). Unlike tau, however, we failed to observe significant correlations between NfL and diffusion metrics, which opposes the data by Ljungqvist et al (69) that showed an association between serum NfL and FA (R 2 = 0.83) 12 months after severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to tau protein, NfL functions as a scaffolding structural protein in axonal and dendritic branching and growth, and NfL undergoes post-translational modification by a series of phosphorylation events, which can make it vulnerable to mechanical stretch and shear stress (62). Growing evidence supports that NfL levels in blood have shown to reflect the progression of neurodegenerative condition (e.g., Alzheimer's disease, multiple sclerosis) ( [63][64][65], differentiate severities of TBI (66), predict clinical outcome (e.g., functional recovery, return-to-play) after severe TBI and concussion (67,68), and correlate with subconcussive head impact exposure (24,26,32,33). Unlike tau, however, we failed to observe significant correlations between NfL and diffusion metrics, which opposes the data by Ljungqvist et al (69) that showed an association between serum NfL and FA (R 2 = 0.83) 12 months after severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the type of contact sport, there seems to be a relationship between NF-L levels and the frequency and magnitude of the head impact [58,[61][62][63][64]151,152]. It is not yet clear, however, whether NF-L may serve as a biomarker for prediction of when it is safe to return to contact sports without the risk of permanent disability and chronic traumatic encephalopathy [153].…”
Section: Traumatic Axonal Injurymentioning
confidence: 99%
“…This implies NF-L levels can be an effective tool at monitoring the severity of SCI accumulation in research settings going forward. A comprehensive study by Rubin et al (2019) compared NF-L with other biomarkers in division 1 football players and found a positive relationship between blood levels of NF-L and frequency of head impacts. Although this study and others use blood serum or plasma to measure NF-L rather than CSF, a strong correlation between the two has been noted (Kawata et al 2018b), further increasing the validity and reliability of NF-L.…”
Section: Sub-concussive Impactsmentioning
confidence: 99%